Low pH-Induced Activation of Single-Atom Pt Sites on TiO2 for Enhanced Photocatalytic H2 Evolution - Kamaleev, Maksim; Kim, Hyesung; Denisov, Nikita; Tesler, Alexander (ACS Applied Energy Materials, 2024)
The application of single atoms (SAs) has emerged as a cutting-edge approach to the cost-efficient utilization of noble metals in catalytic processes. However, the performance of SA systems under various acidity conditions has been barely investigated. Here, we use Pt SA cocatalysts anchored on thin TiO2 films as a model system, which shows a 2.3-3.2-fold enhanced H2 evolution performance at pH = 1, as compared to less acidic conditions (pH = 6 and 14, respectively), with a remarkable turnover frequency (TOF) of up to 589 #H2 site-1 s-1. Based on variations in H2 evolution performance at different pH and Pt loadings, it is clear that activation of additional Pt sites takes place in acidic conditions, which is ascribed to changes in H-binding energy. This allows better utilization of Pt SAs at high loadings and low light intensities. Despite the partial agglomeration of Pt SAs, within 4 h, a steady surface configuration of Pt sites with abundant SAs is established, which correlates with the stabilization of the H2 evolution rate. This research demonstrates a route to extend the limit of photocatalytic H2 generation with suitable SAs and reaction conditions.
CRIS-Team Scopus Importer:2024-10-25
Keywords: hydrogen evolution reaction; pH dependence; photocatalysis; single-atom cocatalysts; TiO